ORTHO-PERIO RELATIONSHIP: IS IT A NUPTIAL KNOT - S.PRIYANKA,; DR.S.P.SARAVANA DINESH,; DR. JAIGANESH RAMAMURTHY, (International Journal of Pharma and Bio Sciences, 2014)
Teeth are responsible for aesthetics and functions such as chewing, speech etc. The thought is that, strong and sound periodontium is required for patients who desire orthodontic treatment. So, are people with poor periodontium denied orthodontic treatment? Or is it vice versa, that is, is orthodontic treatment limited by poor periodontium? This article will give a broad review on the inter relationship between orthodontics and periodontics.